Considerations for Fast Cook‐Off Simulations. Issue 6 (9th November 2016) - Gross, Matthew L.; Hedman, Trevor D.; Meredith, Karl V.
Abstract: Various aspects of fast cook‐off simulations are explored with a spatially one‐dimensional, fully transient numerical model. The model is applied to HMX and consists of equations for the solid (condensed) phase, the gas phase, and the surrounding steel container. The condensed phase HMX decomposition reactions are described by distributed kinetics. The gas phase description includes a detailed chemistry model for the combustion of HMX. Results are presented that outline considerations for simulating fast cook‐off ignition. It is found that small changes in the heat path, such as air gaps, significantly change the predicted ignition time for fast cook‐off, but have minimal effect on slow cook‐off predictions. Simulations indicate that an average heat flux can be used in place of the temporally varying heat flux created by a pool fire. A method is outlined to predict time‐to‐ignition using lab‐scale empirical data instead of directly implementing decomposition kinetics of an energetic material into a simulation. Abstract :